Psychotherapeutic treatments in patients with bipolar and schizoaffective disorders: A meta-analytic review - Hernández-Flórez, Nubia; Klimenko, Olena; Lhoeste-Charris, Alvaro; Rodríguez Ávila, Yildret; Martinez-Gómez, Isneila; Hernández-Flórez, Jorge (Gaceta Médica de Caracas, 2023)
Objective: To analyze scientific publications on bipolarity and schizophrenia to detect both pharmacological and psychotherapeutic treatments that have been applied in the last five years (2018-2022). Method: A quantitative method was applied, under the bibliometric research approach. The PRISMA method was used for this purpose. The search variables and the construction of the equations with their respective Booleans were defined. The database used was the Web of Science (WOS). After filtering by applying exclusion and inclusion criteria, a total of 23 documents were obtained for analysis.